Petrologically controlled oxygen isotopic classification of cogenetic magmatic and metamorphic sapphire from Quaternary volcanic fields in the Eifel, Germany - Schmidt, Sebastian; Hertwig, Andreas; Cionoiu, Katharina; Schäfer, Christof; Schmitt, Axel Karl (Contributions to mineralogy and petrology, 2024)
Gem sapphire is commonly retrieved from primary and secondary deposits associated with alkali basaltic fields, but its source rocks are rarely preserved. The Eifel (Rhenish Massif, western Germany), although not producing gem sapphire, shares many petrologic and geochemical similarities with such fields worldwide. Due to the young age of volcanic deposits and active quarrying, sapphire-bearing rocks are readily accessible, along with detrital sapphire from modern sediments. Here, oxygen isotope and trace element compositions are reported for 223 sapphire grains, and rutile and zircon inclusions in sapphire were dated indicating crystallization synchronous with Paleogene-Quaternary volcanism. Endmembers in δ18O range are sapphires from syenites representing mantle-derived differentiated melts with minor crustal contamination (~4-6‰) and contact metamorphic mica schists (>10‰) as purely crustal source rocks. Intermediate values between ~6 and 10‰ require variable degrees of mantle-crust hybridization. Lower crustal granulite sources are dismissed based on their oxygen isotopic compositions being lower than most sapphire crystals. Diffusion modelling of sharp oxygen isotopic zonation in compositionally zoned crystals precludes crystal residence at >900 °C over the lifetime of evolved magma reservoirs in the Eifel (c. 50 ka). This argues against direct mantle or lower crustal sapphire origins. Instead, low temperature residence is consistent with sharp δ18O gradients, coexisting andalusite, and fluid inclusion barometry. Hence, Eifel sapphire crystallization is attributed to contact metamorphic aureoles around upper crustal (5-7 km) magma bodies where phonolite, trachyte, and carbonatite melts differentiated from mafic parental magmas, and reacted with metasedimentary wall rocks.
Gesehen am 13.01.2025